Antibiotic susceptibility pattern of gram-negative bacterial isolates with special mention on colistin resistance from Intensive Care Unit of a tertiary care hospital: a prospective study assessing the impact of microbial resistance on clinical outcomes - Ravi, Preethika; C. , Ravindranath; S. , Deepa (International Journal of Research in Medical Sciences, 2023)
Background: The frequent use of broad-spectrum antibiotics in ICU leads to increased rates of antimicrobial resistance and occurrence of multidrug-resistant (MDR) micro-organisms. The aim of this study was to evaluate the antimicrobial resistance pattern and colistin susceptibility among bacterial isolates from ICU patients. Method: It is a prospective study with 70 nonrepetitive isolates from ICU samples. The clinical data was obtained from the department records. The gram-negative bacterial isolates were identified by conventional biochemical tests. The antimicrobial susceptibility was determined by Kirby-Bauer disc diffusion method. ESBL producers were detected by double disc diffusion test using ceftazidime, cefotaxime alone and in combination with clavulanic acid. MBL detection was done by imipenem+ EDTA combined disc diffusion test. Colistin sensitivity was determined by broth microdilution according to CLSI guidelines. Results: Out of 70 culture positive specimens. The most common gram-negative bacteria isolated from the samples was Acinetobacter spp. (41%), followed by Klebsiella spp. (20%). Among these 45% were MBL producers, 38.5% were ESBL producers and 14% were both ESBL and MBL producers. Colistin resistance was present among 5.7% isolates in ICU. Conclusions: Non-fermenters were the most common agent causing ICU infections. An alarmingly high rate of resistance to antibiotics especially to colistin in ICU-acquired infections, necessitates new therapeutic strategies to prevent the emergence and control of antimicrobial resistance.